# 1.

2

J.A.Beachy

1

1.2

Primes
from A Study Guide for Beginner’s by J.A.Beachy, a supplement to Abstract Algebra by Beachy / Blair

26. (a) Use the Euclidean algorithm to ﬁnd gcd(1776, 1492). Solution: We have 1776 = 1492 · 1 + 284; 284 = 72 · 3 + 68; 72 = 68 · 1 + 4; 1492 = 284 · 5 + 72;

68 = 4 · 17. Thus gcd(1776, 1492) = 4.

(b) Use the prime factorizations of 1776 and 1492 to ﬁnd gcd(1776, 1492). Solution: Since 1776 = 24 · 3 · 37 and 1492 = 22 · 373, Proposition 1.2.10 shows that gcd(1776, 1492) = 22 . Showing that 373 is prime takes a bit of√ work. You need to check that it is not divisible by any prime number smaller than 373 ∼ 19.3. 27. (a) Use the Euclidean algorithm to ﬁnd gcd(1274, 1089). Solution: We have 1274 = 1089 · 1 + 185; 185 = 164 · 1 + 21; 164 = 21 · 7 + 17; Thus gcd(1274, 1089) = 1. (b) Use the prime factorizations of 1274 and 1089 to ﬁnd gcd(1274, 1089). Solution: Since 1274 = 2 · 72 · 13 and 1089 = 32 · 112 , we see that 1274 and 1089 are relatively prime. 28. Give the diagram of all divisors of 250. Do the same for 484. Solution: The prime factorizations are 250 = 2 · 53 and 484 = 22 · 112 . In each diagram, we need to use one axis for each prime. Then we can just divide (successively) by the prime, to give the factors along the corresponding axis. For example, dividing 250 repeatedly by 5 produces 50, 10, and 2. These numbers go along one side of the rectangular diagram. Divide each of these by 2 to get the opposite side of the diagram. 1089 = 185 · 5 + 164; 17 = 4 · 4 + 1.

21 = 17 · 1 + 4;

250

@

50

@

125 121

@

484

@

242

10

@

25

@

44

@

22

2

@

5

@

4

11

1

@

2

1

29. Find all integer solutions of the equation xy + 2y − 3x = 25.

rewrite that proposition to say that gcd(x.2. y = c. so bc | ad. b) = 1 if and only if gcd(a2 . or x + 2 = −19. Similarly. 2). b. Solution: Assume that b | a and c | a.2. −16).2 J. and so gcd(3n − 1. c) = 1. For each of these values there is a corresponding value for y . Comment: Try to ﬁnd an expression for ad that has bc as a factor. prove that gcd(a. c) = 1.10. we have the four solutions (−1.3 (d) states that gcd(a. c) = 1. for all integers n > 1. 31.Beachy 2 Solution: If we had a product. which shows that gcd(a. Then a similar argument yields gcd(a2 . We can also write d = mb + nc. we could use the prime factorization theorem. Is the same true for 2n − 1 and 3n − 1? Solution: Since (1)(2n − 1) + (−2)(n − 1) = 1. z ) = 1 if and only if gcd(x. y ) = 1 and gcd(x. c) = d. x + 2 = −1. Write b = cq for some integer q . c. then bc | ad. Using Proposition 1. b. and this is equivalent to gcd(a2 . By Euclid’s lemma. (17. 30. b2 ) = 1. then gcd(a. and z = q . 33. 2n − 1) = 1. q ∈ Z. Listing the solutions as ordered pairs (x. For positive integers a. That motivates one possible method of solution. prove that if gcd(a. xy + 2y − 3x = 25 (x + 2)y − 3(x + 2) = 19 (x + 2)(y − 3) = 19 (x + 2)y − 3x − 6 = 25 − 6 (x + 2)y − 3x = 25 Now since 19 is prime. Using c = b gives gcd(a. b) = 1 and gcd(a. bc) = 1 if and only if gcd(a. so that a = bp and a = cq for some p. 32. . cq ) = 1. b2 ) = 1 if and only if gcd(a. (2)(3n − 1) + (−3)(2n − 1) = 1. x + 2 = 19. Solution: To help you see why this is a consequence of Proposition 1. Prove that if b | a and c | a and gcd(b.2. then gcd(a. for some m. b2 ) = 1 if and only if gcd(a. b) = 1 and c | b.3 (d). 4). b) = 1 if and only if a and b have no prime divisors in common. Prove that n − 1 and 2n − 1 are relatively prime. b.3 (c).A. b2 ) = 1. n − 1) = 1.3 (d). For positive integers a. yz ) = 1. we have gcd(2n − 1. the only way it can be factored is to have 1 · 19 = 19 or (−1) · (−19) = 19. Solution: Proposition 1. this happens if and only if a2 and b2 have no prime divisors in common. Then ad = mba + nca = mb(cq ) + nc(bp) = (mp + nq )(bc). Therefore we have 4 possibilities: x + 2 = 1. b) = 1.2. c be nonzero integers. n ∈ Z . Alternate Solution: It is also possible to use Proposition 1. and (−21. (−3.1. Note: This extends Proposition 1. b) = 1 means that gcd(a. If we let x = a.2. this implies that gcd(a. b2 ) = 1. 22). Let a. since the complementary factor must be equal to y − 3. y ).

and you might still ask if there is a general principle involved here. 2n − 1) = 1. then gcd(2m − 1. Let m and n be positive integers. then there exist a. 2n − 1) = 1. n) = 1 and showing Before beginning the proof. n) = 1. 1. 35. that this forces gcd(2m − 1. n) = d. we will use a proof by contradiction. then there exist p. 2n − 1) = gcd(2n − 1. . n) = 1. for some t ∈ Z. you don’t have to explain how you found them. n − 1) = gcd(n − 2. n − 1) and so we can use Problem 33 to conclude that 2n2 + 4n − 3 and 2n2 + 6n − 4 are relatively prime since 2n − 1 and n − 1 are relatively prime. Prove that gcd(2m − 1.2 J. then gcd(m. and this completes the proof. 2n − 1) = 1 if and only if gcd(m. To prove the conassuming that gcd(m. for all integers n > 1. n) = 1. 1) = 1. two parts. b ∈ Z with am + bn = 1. 2n2 + 6n − 4) = 1. 2n2 + 4n − 3) = gcd(2n2 + 4n − 3. 2n − 1) = 1. The next step is to divide 2n2 + 4n − 3 by 2n − 1. 34. Solution: We can use the Euclidean algorithm. that’s because it probably is. 2n − 1) which states that if gcd(2m − 1. We have 1 = 21 − 1 = 2am+bn − 2bn + 2bn − 1 = 2bn (2am − 1) + 2bn − 1 = 2bn (s)(2m − 1) + (t)(2n − 1) If gcd(m. But then an argument similar to the one given for the ﬁrst part shows that 2d − 1 is a common divisor of 2dq − 1 and 2dp − 1. First. remember (from calculus. n) = 1. This argument shows that gcd(2n2 + 6n − 4. n) = 1. say gcd(m. 2n − 1) = verse.1.Beachy 3 Comment: Is this really a proof? Yes–producing the necessary linear combinations is enough. Therefore gcd(2m − 1. in trying to ﬁnd a linear combination that eliminates the variable n. we will prove that if = 1. Comment: We need to do the proof in gcd(m. Comment: You could also continue on with the Euclidean algorithm. The proof now involves what may look like a trick (but this time it is a useful one). for some s ∈ Z. The same argument shows that we can write 2bn − 1 = (2n − 1)(t). Prove that gcd(2n2 + 4n − 3. If this proof just looks like a trick. which proves that gcd(2m − 1. Then we will prove the converse. and so we have found a linear combination of 2m − 1 and 2n − 1 that equals 1. and this gives a quotient of n + 2 and a remainder of n − 1. say 2am − 1 = (2m − 1)(s). Substituting x = 2m and k = a in the identity given above in the comment shows that 2m − 1 is a factor of 2am − 1. to obtain gcd(2n − 1. Maybe there is a bit of justiﬁcation. if not from high school algebra) that xk − 1 = (x − 1)(xk−1 + xk−2 + · · · + x + 1) holds for all values of x: Solution: If gcd(m.A. q ∈ Z with m = dq and n = dp. Long division of polynomials shows that dividing 2n2 + 6n − 4 by 2n2 + 4n − 3 gives a quotient of 1 and a remainder of 2n − 1.

for some integers k and q . b.3. c. then k − q has 2 as a factor. Prove or disprove that if gcd(b. c)? Answer: Yes. then m2 − n2 is divisible by 8. 575 37. Show that gcd(11n + 5. If k − q is even. Answer: 475 = 52 · 19. Comment: There is a more elegant solution in §1. c).41. 2n). then m2 − n2 is divisible by 8. y of the equation xy + 5x − 8y = 79. say k − q = 2p. Part (b): Let a.1. Prove that if m and n are odd integers. Find all positive integer solutions x. Hint: Look for a counterexample. b. Hint: Look at the common prime divisors of a. 180) = 22 · 32 = 36. for some integer p. gcd(5917. Does gcd(a. then gcd(a. Find the prime factorizations of 5917 and 4331 and use them to ﬁnd gcd(5917. c be positive integers with a2 + b2 = c2 . gcd(475.2 J. Part (b): Let a.26. (See Problem 1. so it has 2 as a factor. so it must also be odd.3. 385 = 5 · 7 · 11. lcm[252. c be positive integers. 45.Beachy 4 36. we can write m = 2k + 1 and n = 2q + 1. bc) = gcd(ab. 180] = 22 · 32 · 5 · 7 = 1260 42. Now we need to take two cases. m2 − n2 = (4)(2t)(k − q ) = (8)(t)(k − q ) . .A. Answer: The positive solutions are x = 9.1. Hint: See the solution to Problem 29. Find the prime factorizations of 252 and 180 and use them to compute the greatest common divisor and least common multiple of 252 and 180. Now we can suppose that k + q + 1 = 2t. which can be given after some new techniques have been developed. Then m2 − n2 = (2k + 1 + 2q + 1)(2k + 1 − 2q − 1) = (4)(k + q + 1)(k − q ) . 4331). y = 8.) Solution: Since m. 7n + 3) is 2 if n is odd and 1 if n is even. then k + q = (k − q ) + (2q ) is the sum of an odd integer and an even integer. 7n + 3) = gcd(n + 1. c) = 1. y = 34 and x = 11. (See the solution to Problem 35. b) = gcd(a. That means that k + q + 1 is even. 4331 = 61 · 71. Hint: Use the Euclidean algorithm to show that gcd(11n + 5. If k − q is odd. Find the prime factorizations of 475 and 385 and use them to compute the greatest common divisor and least common multiple of 475 and 385. substituting for k + q + 1 gives us Showing that we can factor 8 out of m2 − n2 gives exactly what we were to prove: if m and n are odd. for some integer t. 180 = 22 · 32 · 5 gcd(252.) ANSWERS AND HINTS 39. 4331) = 61 38. Answer: 5917 = 61 · 97. In this case. 385) = 5. b.) 43. 385] = 52 · 7 · 11 · 19 = 36. Substituting for k − q gives us m2 − n2 = (4)(k + q + 1)(2p) = (8)(k + q + 1)(p) . (Compare Problem 1. lcm[475. Answer: 252 = 22 · 32 · 7. 46. n are odd.